Traceability of pasture feeding using some fatty acids and spectrophotometric parameters in milk - Marcella Avondo; Renato Italo Pagano (Italian Journal of Animal Science, 2010)
Seventy-three cow milk individual samples deriving from seven farms with different feeding system (pasture, P vs. stall, S), were collected with the aim to trace pasture feeding from different milk characteristics. Samples were analyzed for: linoleic and linolenic acids, colour parameters (L*, b*, a* C and H) using a Minolta CM-2002 spectrophotometer; the integral value of reflectance spectrum between 530 and 450 nm was also calculated. The linoleic/linolenic acids ratio resulted significantly lower in P group (P<0.001), whereas yellowness (b*) and the absolute integral value resulted significantly higher in P group (P<0.001). Linoleic/linolenic acids ratio allowed the complete discrimination between feeding groups, whereas the integral value and yellowness allowed only a partial discrimination (respectively 90.4% and 79.5% of cases). However, a milk fatty acid composition is strongly dependent on fat intake, any additional fat inclusion in the ration can modify it, apart from pasture presence in the diet. On the contrary integral value and yellowness are strongly related to carotenoids pigments, recognized as biomarkers of fresh herbage in the diet. For these reasons, integrating linoleic/linolenic ratio and colour parameters in a principal components analysis, a complete discrimination between pasture and stall feeding was obtained, with a greater reliability of results due to the combination of milk characteristics associated to different sources of variation (fats intake and carotenoids intake).